Microglial expression of GAT‐1 in the cerebral cortex. Issue 3 (6th November 2019) - Fattorini, Giorgia; Catalano, Myriam; Melone, Marcello; Serpe, Carmela; Bassi, Silvia; Limatola, Cristina; Conti, Fiorenzo
Abstract: Microglial cells are the immune cells of the brain that, by sensing the microenvironment, permit a correct brain development and function. They communicate with other glial cells and with neurons, releasing and responding to a number of molecules that exert effects on surrounding cells. Among these, neurotransmitters and, in particular, gamma‐aminobutyric acid (GABA) has recently gained interest in this context. We demonstrated the expression of GABA transporter 1 (GAT‐1) in microglial cells both in soma and cell processes. We show that microglial cell treatment with 1, 2, 5, 6‐tetrahydro‐1‐[2‐[[(diphenylmethylene)amino]oxy]ethyl]‐3‐pyridinecarboxylic acid hydrochloride (NNC‐711), a potent and selective GAT‐1 inhibitor, significantly reduced Na + ‐dependent GABA uptake. On the other hand, GABA uptake was significantly increased by cell treatment with ( S )‐1‐[2‐[tris(4‐methoxyphenyl)methoxy]ethyl]‐3‐piperidinecarboxylic acid (SNAP‐5114), a GAT‐2/3 inhibitor, and this effect was completely blocked by the botulinum toxin BoNT/C1, that specifically cleaves and inactives syntaxin 1A (STX1A). Overall, these findings show that microglial cells express GAT‐1 and indicate that STX1A plays an important role in the regulation of GAT‐1‐dependent GABA uptake in microglia. Main points: Microglia express GAT‐1. GAT‐1 regulation in microglia is mediated by STX1A.